Hubungan Dukungan Keluarga dengan Tingkat Kecemasan Pasien Pre Operasi: Relationship Between Family Support and Levels of Anxiety in Pre-Operative Patients - Roni, Muhammad; Indraswati, Ita; Sarifah, Siti; Purwaningsih, Heni; Sari, Anggi Luckita (Jurnal Sains dan Kesehatan, 2026)
Surgery is a medical procedure aimed at repairing a specific part of the body that is experiencing problems. Surgical procedures can affect patients psychologically. Patients often experience excessive anxiety before entering the operating room. High levels of anxiety can cause discomfort that affects the physical and mental condition of patients. Therefore, to overcome preoperative anxiety, an effective strategy is needed, namely through family support. The purpose of this study was to determine the relationship between family support and the level of preoperative anxiety in patients. This was a correlational study with a sample of 81 patients who underwent surgery at PKU 'Aisyiyah Boyolali Hospital. The sampling technique used was purposive sampling. The research instruments used were questionnaires on family support and anxiety. Data analysis was performed using the Spearman Rank test. The results of the Spearman rank test analysis showed r 0.415 with a p-value of 0.00 < 0.05, indicating that Ha was accepted, r 0.415, thus showing a significant relationship between family support and the level of anxiety in preoperative patients at PKU Aisyiyah Hospital in Boyolali. Keywords:          Family Support, Preoperative Patient Anxiety Level   Abstrak Pembedahan adalah prosedur medis bertujuan memperbaiki bagian tertentu yang mengalami masalah. Tindakan pembedahan dapat mempengaruhi psikologis pasien, Pasien sering cemas berlebihan sebelum menuju ruang operasi. Tingkat kecemasan yang tinggi dapat menyebabkan ketidaknyamanan yang mempengaruhi kondisi fisik dan mental pasien. Oleh karena itu, untuk mengatasi kecemasan pre operasi diperlukan strategi yang efektif yaitu melalui dukungan keluarga. Tujuan penelitian ini untuk mengetahui hubungan dukungan keluarga dengan tingkat kecemasan pasien pre operasi. Desain penelitian korelasional, sampel penelitian ini adalah 81 pasien yang dilakukan tindakan operasi di Rumah Sakit PKU ‘Aisyiyah Boyolali. Teknik pengambilan sample dengan purposive sampling. Instrumen penelitian ini menggunakan kuesioner dukungan keluarga dan kecemasan. Analisa data menggunakan uji Spearman Rank. Hasil analisa uji statistic spearman rank  r 0.415 dengan p value 0,00 < 0,05 menunjukkan Ha diterima, r 0,415 sehingga terdapat hubungan yang signifikan antara dukungan keluarga dengan tingkat kecemasan pasien pre operasi di Rumah Sakit PKU Aisyiyah Boyolali. Kata Kunci:         Dukungan Keluarga, Tingkat Kecemasan Pasien Pre Operasi